2018
DOI: 10.1177/2325967118810176
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Virtual Arthroscopic Simulator for Orthopaedic Surgery Residents by Year in Training

Abstract: Background:Virtual reality arthroscopic simulators are an attractive option for resident training and are increasingly used across training programs. However, no study has analyzed the utility of simulators for trainees based on their level of training/postgraduate year (PGY).Purpose/Hypothesis:The primary aim of this study was to determine the utility of the ArthroS arthroscopic simulator for orthopaedic trainees based on their level of training. We hypothesized that residents at all levels would show similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…Second, some participants acknowledged that it was difficult for them to acquire their skills within a fixed time interval owing to a heavy clinical workload. Since it has been suggested that incorporating an irregular learning interval is more effective in maintaining skills over the long term, 23 further research should also focus on an irregularly spaced retraining model. Third, we evaluated our spaced retraining schedule over the course of just 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some participants acknowledged that it was difficult for them to acquire their skills within a fixed time interval owing to a heavy clinical workload. Since it has been suggested that incorporating an irregular learning interval is more effective in maintaining skills over the long term, 23 further research should also focus on an irregularly spaced retraining model. Third, we evaluated our spaced retraining schedule over the course of just 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…Perfect scores were established initially and their validity demonstrated by previous studies. 22,23 Immediately after the massed learning phase, a pretest, task 8, was performed by each participant. During the pretest, participants were required to perform the same process as in task 7.…”
Section: Simulation Trainingmentioning
confidence: 99%
“…Surgery training systems provide users with a non‐invasive, safe, user‐friendly, and efficient simulation training environment, which is more convenient than traditional training for users to repeat exercises at any time, and they can potentially improve and shorten the learning curve of users and help users gradually transition from virtual to real patients. More importantly, surgery training systems as a training tool help to cultivate and improve the user's surgery skills 26‐29 …”
Section: Computer‐assisted Orthopaedic Surgery Training Systemsmentioning
confidence: 99%
“…These types of simulators offer the advantages of both systems, namely haptic feedback, real-life surgical material, realistic internal views, and training of different scenarios. For training in arthroscopic skills, knee and shoulder arthroscopy simulators based on VR are of interest [32] .…”
Section: Knowledge and Trainingmentioning
confidence: 99%